Shifting gender relations in agriculture and irrigation in the Nepal Tarai-Madhesh - Karn, Sujeet; Sugden, Fraser; Sah, K.K.; Maharjan, J.; Shah, T.N.; Clement, Floriane (International Water Management Institute, 2020)
This report explores how women perceive participation and empowerment vis-a-vis access to water and other agricultural resources in the Tarai/Madhesh of Nepal. The report argues that gendered vulnerability is indeed intricately connected with other axes of difference, such as caste and economic status, despite women’s critical role in agricultural production and their active engagement in access to water and irrigation in agriculture. Overall, women’s well-being seems to have decreased as a consequence of male out-migration. However, there are women who have also become empowered in new ways, taking up enterprise opportunities.